Opinions of traditional and nontraditional female students as expressed among and toward each other in a selected postsecondary educational institution. - Krittenbrink, Juanita Wittrock (My University, 1983)
A total of one hundred and forty-six (146) respondents completed the "Demographic Background Information" page and the "Opinion of Self and Others" questionnaire. Reliability of the opinions instrument was established and the statistical treatment applied included the usage of the chi-square tests for the frequency distribution. The .05 level of significance established the significant difference and sixteen (16) of the forty-five (45) questions from the opinions questionnaire showed significant differences.

The final indications showed that women, of all ages, enjoyed either entering or re-entering the specific educational institution. Although age did prove to be a factor, it was not a restrictor as all ages of the women students seemed very enthusiastic in continuing their education.

The three (3) age divisions for the study were: "Younger" women students (ages 18 - 24 years); "Middle-Aged" students (ages 25 - 34 years); and "Older" students (ages 35 years and beyond). Significant differences in opinions were held among the ages in relation to the following: Self-concept, Competitiveness, Family, Treatment of Students, and Time Commitment.

This study was designed to examine the different opinions women students hold among and toward each other with age as the primary consideration. The eight (8) basic areas of concern were: (1) self-concepts; (2) intelligence; (3) educational goals; (4) competitiveness; (5) family concerns; (6) treatment; (7) time commitment; (8) monetary commitment.
Opinions of traditional and nontraditional female students ...
Keywords: Education, Secondary.